PERSEPSI ANGGOTA KELOMPOK TANI TERHADAP PERAN PENYULUHAN PERTANIAN DALAM MENINGKATKAN PRODUKSI USAHATANI PADI SAWAH - Martinus N. Dapa; Serman Nikolaus; Selfius P. N. Nainiti (Undana Press, 2021)
This research has been carried out in Tarus Village, Middle Kupang Subdistrict, Kupang Regency from April to May 2019 with the aim of: (1). Understanding perceptions of members of farmer groups toward the role of extension workers in increasing the production of lowland rice farming and. (2). Understanding the problems faced by farmers in increasing the production of lowland rice farming. The research method used in this study is a survey method. Samples used in this study were 32 farmers taken from one farmer group using the census method (saturated sampling). The type of data collected are primary data coluted by direct interviews with respondents guided by the questionnaire, while secondary data are obtained from searching written documents, related agencies and literature related to this study. The results of the analysis show that: (1) the perception of members of farmer groups toward the role of agricultural extension in the Village of Tarus is classified as high category wich is the persentase of mean score in reacing the maximum score is 74.85%. This is evident from the fact that 32 members of the respondent farmer group there were 9 respondent farmers in (28.12%) had a fairly good perception, as many as 20 respondent farmers (62.5%), had a good perception and as many as 3 respondent farmers (9.38%) is Very good perception (2). Some respondent farmers experienced constraints in extension activities or farming activities such as limited capital. There are members of farmer groups who do not understand when attending counseling. Lack of facilities provided by extension agents, late in overcoming farmers' problems.